Fast flaring observed from XMMU J053108.3-690923 by eROSITA: a supergiant fast X-ray transient in the Large Magellanic Cloud - Maitra, C.; Haberl, F.; Vasilopoulos, G.; Ducci, L.; Dennerl, K.; Carpano, S. (Astronomy and Astrophysics, 2021)
Context. Supergiant fast X-ray transients (SFXTs) are a peculiar class of supergiant high-mass X-ray binary (HMXB) systems characterised by extreme variability in the X-ray domain. In current models, this is mainly attributed to the clumpy nature of the stellar wind coupled with gating mechanisms involving the spin and magnetic field of the neutron star. Aims: We studied the X-ray properties of the supergiant HMXB XMMU J053108.3-690923 in the Large Magellanic Cloud to understand its nature. Methods: We performed a detailed temporal and spectral analysis of the eROSITA and XMM-Newton data of XMMU J053108.3-690923. Results: We confirm the putative pulsations previously reported for the source with high confidence, certifying its nature as a neutron star in orbit with a supergiant companion. We identify the extremely variable nature of the source in the form of flares seen in the eROSITA light curves. The source flux exhibits a total dynamic range of more than three orders of magnitude, which confirms its nature as an SFXT, and is the first such direct evidence from a HMXB outside our Galaxy exhibiting a very high dynamic range in luminosity as well as a fast flaring behaviour. We detect changes in the hardness ratio during the flaring intervals where the hardness ratio reaches its minimum during the peak of the flare and increases steeply shortly afterwards. This is also supported by the results of the spectral analysis carried out at the peak and off-flare intervals. This scenario is consistent with the presence of dense structures in the supergiant wind of XMMU J053108.3-690923 where the clumpy medium becomes photoionised at the peak of the flare leading to a drop in the photo-electric absorption. Further, we provide an estimate of the clumpiness of the medium and the magnetic field of the neutron star assuming a spin equilibrium condition.
Keywords: Astrophysics - High Energy Astrophysical Phenomena; Magellanic Clouds; stars: neutron; supergiants; X-rays: binaries